A training paradigm to enhance performance and safe use of an innovative neuroendovascular device. Issue 1 (1st January 2016) - Ricci, Donald R.; Marotta, Thomas R.; Riina, Howard A.; Wan, Martina; De Vries, Joost
Abstract : Training has been important to facilitate the safe use of new devices designed to repair vascular structures. This paper outlines the generic elements of a training program for vascular devices and uses as an example the actual training requirements for a novel device developed for the treatment of bifurcation intracranial aneurysms. Critical elements of the program include awareness of the clinical problem, technical features of device, case selection, and use of a simulator. Formal proctoring, evaluation of the training, and recording the clinical outcomes complement these elements. Interventional physicians should embrace the merits of a training module to improve the user experience, and vendors, physicians, and patients alike should be aligned in the goal of device training to improve its success rate and minimize complications of the procedure.